The Influence of Bottom Ash Column in the Geotechnical Properties Enhancement of Soft Clay Soil - Ng, Jun Shen; Muzamir, Hasan; Nur Amina Azmyra, Hashim (International Journal For Multidisciplinary Research, 2023)
The utilization of bottom ash in ground improvement studies can cut down the quantity of generated waste which is in response to environmental conservation and enhancing the soil properties. The bottom ash which plays the role of replacing the coarse aggregate like sand and gravel in upgrading the behaviour of soft clay soil can fulfill the sustainability concept in construction. For construction purposes, the soil and ground improvement activities are necessary to carry out by using the relevant techniques, including the vibro-replacement method. This method was applied which suits the limitation of this study as it was executed in the laboratory for the preparation of the bottom ash column. The properties examination of kaolin clay and bottom ash were first studied through its particle size, specific gravity, liquid and plastic limit, and compaction. The following procedure was about the column preparation process, where the column diameter was set to be constant at 20 mm throughout the study. The execution of the Unconfined Compression Test (UCT) on the Bottom Ash Column has shown its impact on the undrained shear strength upgrade and it was focused on the height of the bottom ash column built beneath the kaolin clay at 60mm, 80mm, and 100 mm. As observed from the trend, the height of the bottom ash column shows a direct proportional relationship by the undrained shear strength, ranging from 11.64% - 14.26% by using the control sample (with no bottom ash reinforcement) as reference. Conclusively, the use of bottom ash subsides the disposal waste and in no time provides support to the shear strength of soft clay soil which is sustainable and applicable.